"FORMATION OF INDEPENDENT EDUCATION OF STUDENTS BASED ON TIME MANAGEMENT TECHNOLOGIES" - Otajonova Maftuna Sultonmurodovna (International Journal of Innovations in Engineering Research and Technology, 2022)
This article talks about the methods of correct and accurate organization and implementation of independent studies of students of higher education institutions, development of independent research of students based on time management technologies.